Going into trade fairs (ITC GenevaCH, 1982)
Handbook on techniques for participating in trade fairs with particular reference to exporters and trade promotion organizations in developing countries. Contains 26 articles (previously appearing in `International Trade FORUM') on objectives of participating; publicity; practical aspects of designing, preparing and operating a stand; relations with visitor handling enquiries; and evaluating results. Emphasis is on the practical aspects facing trade promotion organizations and enterprises in developing countries wishing to participate in a trade fair, possibly for the first time.
Includes bibliographical references